2010
DOI: 10.1103/physrevb.81.094115
|View full text |Cite
|
Sign up to set email alerts
|

From antiferromagnetism to superconductivity inFe1+yTe1xSex

Abstract: The nuclear and magnetic structure of Fe 1+y (Te 1-x ,Se x ) (0 ≤ x ≤ 0.20) compounds was analyzed between 2 K and 300 K by means of Rietveld refinement of neutron powder diffraction data.Samples with x ≤ 0.075 undergo a tetragonal to monoclinic phase transition at low temperature, whose critical temperature decreases with increasing Se content; this structural transition is strictly coupled to a long range antiferromagnetic ordering at the Fe site. Both the transition to a monoclinic phase and the long range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
192
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(226 citation statements)
references
References 23 publications
(56 reference statements)
33
192
1
Order By: Relevance
“…Due to the fact that the studied here subtle FS changes are closely related to geometry of the u.c. of this compound, the experimental lattice parameter c [31] …”
Section: Resultsmentioning
confidence: 99%
“…Due to the fact that the studied here subtle FS changes are closely related to geometry of the u.c. of this compound, the experimental lattice parameter c [31] …”
Section: Resultsmentioning
confidence: 99%
“…11,25,28 For y < y c ≈ 0.1, the structure is monoclinic, with two different Fe-Fe in-plane bond lengths that match up with the alternating antiferromagnetic and ferromagnetic bonds of the collinear magnetic structure. 11,18,41 For y > y c , the structure is orthorhombic, with a single Fe-Fe bond length; the corresponding magnetic structure is found to be helical. 11, 25 Mizuguchi et al 28 have recently demonstrated with high-resolution x-ray diffraction that the boundary between the orthorhombic and monoclinic phases can also be crossed as a function of temperature for y y c .…”
Section: A Tuning Of the Magnetic Ordermentioning
confidence: 99%
“…The excess Fe resides in an interstitial site centered above (or below) a plaquette of four Fe sites. 18,19 The magnetic interaction between an interstitial and the Fe nearest-neighbors results in locally ferromagnetic correlations 20,21 and weak localization of the charge carriers, 22 and acts as a magnetic electron donor. 22 The excess Fe concentration is anticorrelated with the superconducting volume fraction and results in short-range magnetic order.…”
mentioning
confidence: 99%
“…It is clear that the RQP regime is not developed as for samples S02 to S07, but it may produce an additional conduction that impedes to describe the temperature dependence of its resistivity with a simple expression. (FTSe) [16,33,34,17], FeTe 1−x S x (FTS) [35] and FTSeS (our work). The data point of the S01 sample is indicated with an arrow.…”
Section: Resultsmentioning
confidence: 99%